Ascaris lumbricoides infection: Still a threat for iron deficiency anaemia in 2-year-old Bangladeshi slum-dwelling children - Hossain, Md. Shabab; Das, Subhasish; Gazi, Md. Amran; Mahfuz, Mustafa; Ahmed, Tahmeed (The Journal of Infection in Developing Countries, 2019)
Introduction: Although parasitic infections lead to extracorporeal iron loss resulting in iron deficiency anaemia (IDA), data associating IDA with parasitic infections in the first two years of life are limited. We sought to evaluate the prevalence and severity of anaemia and IDA during this period and to investigate the association between intestinal parasitic infections and IDA. Methodology: Data was collected under MAL-ED study protocol in Bauniabadh slum of Dhaka, Bangladesh. The presence of parasites in stool was detected using wet preparation microscopy at 7, 15, and 24 months. Anaemia was defined as serum haemoglobin < 11 g/dL and IDA was defined by serum haemoglobin < 11 g/dL, serum ferritin < 12 g/L and soluble transferrin receptor > 8.3 mg/L. Logistic regression was done to quantify the relation between stool parasite and IDA separately on samples collected at 7, 15 and 24 months. Results: 265 children were enrolled after birth and samples were collected at 7, 15 and 24 months. Anaemia was detected at 7, 15 and 24 months in 117 (48.8%), 106 (44.2%) and 67 (27.9%) cases whereas IDA was found in 15 (6.3%), 47 (19.6%) and 39 (16.3%) cases, respectively. Iron deficiency anaemia at 24 months was significantly associated with Ascaris lumbricoides infection (OR 3.76; 95 % CI, 1.08-13.11). Conclusions: The prevalence of anaemia and IDA in slum dwelling children of Dhaka is high and Ascaris lumbricoides infection was found to have a strong association with IDA at 24 months of age.